LITERATURE OF REVIEW ANALYSIS OF PRODUCTION EXPENSES, INVESTMENT EXPENSES, OPERATIONAL EXPENSES ON NET PROFIT OF PT INDUSTRI JAMU DAN FARMASI SIDOMUNCUL Tbk. 2018-2022 - Arla Septavi Alya Lestari; Muhammad Richo Rianto (Draf Solusi Indonesia, 2023)
This research aims to test whether production costs,investment costs, sales operational costsinfluencenot a professionalat PT INDUSTRI JAMUAND FARMASI SIDOMUNCUL Tbk. 2018-2022. Thisresearch uses quantitative data samples andsampling uses purposive sampling techniques. Thedata analysis technique in this research uses multiplelinear regression and classical assumption tests. Dataprocessing in this research was assisted by the IBMSPSS 26 tool